PENGARUH GAJI DAN MOTIVASI KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT. SINAR FAJAR CAHAYA ABADI MEDAN - Denny Denny; Thomas Sumarsan Goh; Errie Margery (JURNAL BISNIS KOLEGA, 2021)
PT. Sinar Fajar Cahaya Abadi Medan is a company engaged in the trading of large machinery and spare parts. One form of decline in employee work productivity in the company can be seen from the decreased number of sales and service activities.The population in this study were all employees at the company, amounting to 30 people. Samples were taken with a saturated sampling technique in which all members of the population were used as samples. Thus, the sample in this study amounted to 30 people.The simultaneous hypothesis test results show that salary and work motivation have a positive and significant effect on work productivity at PT. Sinar Fajar Cahaya Abadi Medan. The partial hypothesis test results show that each variable salary and work motivation have a positive and significant effect on work productivity at PT. Sinar Fajar Cahaya Abadi Medan.Â Keywords: Salary, Work Motivation, Work Productivity.